2006
DOI: 10.1002/ijc.22027
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional census of 36 microdissected colorectal cancers yields a gene signature to distinguish UICC II and III

Abstract: UICC stage II and III colorectal cancers (CRC) differ fundamentally in prognosis and therapeutic concepts. To analyze differential gene expression between both stages and to establish a relationship between molecular background and clinical presentation, tumor material from 36 unselected consecutive patients presenting with sporadic CRC, 18 UICC stage II and 18 UICC stage III, were laser microdissected to separate epithelial tumor cells. Gene expression levels were measured using U133A Affymetrix gene arrays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
(24 reference statements)
0
24
0
Order By: Relevance
“…CRIP1 overexpression has also been demonstrated to be the most highly differentially expressed gene in invasive cervical carcinomas; 100-fold up-regulation relative to normal cervical keratinocytes measured in 34 cervical tissues from different clinically defined stages [5],[6]. CRIP1 was also found to have high levels of expression in pancreatic adenocarcinoma, lung cancers and colorectal cancers [7][9]. These data strongly support the development of imaging probes targeting CRIP1 to improve cancer detection.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…CRIP1 overexpression has also been demonstrated to be the most highly differentially expressed gene in invasive cervical carcinomas; 100-fold up-regulation relative to normal cervical keratinocytes measured in 34 cervical tissues from different clinically defined stages [5],[6]. CRIP1 was also found to have high levels of expression in pancreatic adenocarcinoma, lung cancers and colorectal cancers [7][9]. These data strongly support the development of imaging probes targeting CRIP1 to improve cancer detection.…”
Section: Introductionmentioning
confidence: 76%
“…Human CRIP1, primarily a cytosolic protein, was cloned in 1997 [1] using RT-PCR of human small intestine RNA and oligonucleotides whose sequence was derived from the human heart homolog of this protein, CRHP [2]. Recently CRIP1 has been identified as a very exciting biomarker for human breast cancers [3],4, cervical cancers [5],[6], pancreatic cancers [7],[8] and potentially other cancers [4],[9]. In experiments comparing CRIP1 expression in human breast cancer to matched normal breast tissue the mRNA for this target was overexpressed 8–10-fold in approximately 90% of both invasive and ductal carcinoma in situ [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, deregulated CRIP1 expression was reported to characteristically occur in several malignant tumors, including breast, cervical, prostatic, colorectal, and pancreatic cancer [9, 11, 12, 14, 15]. Interestingly, CRIP1 was also considered a bone-specific breast cancer metastasis gene [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…CRIP1 may be involved in intestinal zinc transport [10, 13-15], and is observed to be overexpressed in various types of tumors [16-22] including breast cancer [20, 21], osteosarcoma [19], prostate cancer [17], pancreatic cancer [16], and colorectal cancer [23]. Numerous studies have indicated that CRIP1 is an important transcriptional regulation factor during tumor development.…”
Section: Introductionmentioning
confidence: 99%